2010
DOI: 10.1186/2047-783x-15-5-214
|View full text |Cite
|
Sign up to set email alerts
|

Impact of platelet count on results obtained from multiple electrode platelet aggregometry (Multiplate™)

Abstract: Objectives Use of potent antiplatelet drugs requires evaluation of platelet function. While platelet function in elective cases is usually assessed in a central laboratory environment, there is also an urgent need for rapid perioperative point-of-care assessment. Recently, multiple electrode platelet aggregometry has been developed and assumed to measure platelet function independent from platelet count. We tested the hypothesis that results of multiple electrode platelet aggregometry are affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 19 publications
5
85
3
2
Order By: Relevance
“…These results extend our recent findings of a very high reproducibility of the VerifyNow Ò assay compared with MEA and other platelet function tests [23]. Moreover, a very recent study on 20 healthy volunteers reported that results obtained using MEA are significantly affected by variations in platelet count below the normal range [24]. Our study extends these findings to CAD patients with normal platelet counts.…”
Section: Platelet Turnover and Platelet Aggregation In Whole Bloodsupporting
confidence: 90%
“…These results extend our recent findings of a very high reproducibility of the VerifyNow Ò assay compared with MEA and other platelet function tests [23]. Moreover, a very recent study on 20 healthy volunteers reported that results obtained using MEA are significantly affected by variations in platelet count below the normal range [24]. Our study extends these findings to CAD patients with normal platelet counts.…”
Section: Platelet Turnover and Platelet Aggregation In Whole Bloodsupporting
confidence: 90%
“…Mengistu blood aggregometry at lower platelet concentrations [19,20]. Two more studies also reported correlations between platelet count and extent of platelet aggregation on MEA [18,21]. However, the latter results are difficult to interpret as the counts were adjusted either by addition of PPP [21], which is known to inhibit platelet aggregation [17], or with dilution with Tyrode's buffer [18].…”
Section: Discussionmentioning
confidence: 99%
“…Platelet aggregation was measured using a lumi-aggregometer (Chrono-log Corp., Havertown, PA, USA) and was monitored for 8 min. The area under the aggregation curve was calculated by Image-Pro Plus software (Media Cybernetics, Silver Spring, MD, USA) for statistical analysis as previously described (Hanke et al, 2010).…”
Section: Platelet Aggregationmentioning
confidence: 99%